Vietnam poverty update report 2006 : (National Political Publishers, 2007)
Vietnam Poverty Update Report 2006 aims to provide an updated picture of the poverty situation in Vietnam since the early 1990s. Trends in poverty reduction along with appropriate policy implications are assessed using household survey datasets and other sources of information, including the results of the various studies available to date. In contrast to the above mentioned reports, the preparation and consultation progress for this report was coordinated by Vietnamese research institutions led by the Vietnamese Academy of Social Sciences, with technical assistance from the World Bank in Vietnam.